Correlation between Knowledge and the Adherence to Take Antihypertensive Medication for Elderly Hypertensive Patients in Krian Public Health Center Sidoarjo Regency - Sukma Sahadewa; Kadek Dwipa; Gede Abi Yoga; Mandasari Dwi Pertiwi (Berkala Kedokteran, 2019)
Abstract: Hypertension is a condition of elevated abnormal arterial blood pressure that lasts persistently. Some knowledge that should be known by hypertensive patients are such as the meaning of hypertension, the cause of hypertension, the symptoms that come along, and the importance of regular and long term treatment, also knowing the dangers posed if not taking the medication. This study aims to determine the correlation between knowledge and adherence to taking antihypertensive medication in elderly hypertensive patients at the Krian Public Health Center, Sidoarjo Regency. In this study, the population was elderly hypertensive patients who examined themselves or only took control to take medication at the Elderly Polyclinic of Krian Public Health Center in Sidoarjo Regency with 332 populations with 75 samples taken. The result of this research was obtained sig. value = 0,000 (<0,05). This study used the Spearman Correlation statistical test in analyzing the data. From the results of this study it was concluded that there was a relationship between knowledge and adherence to taking antihypertensive medication in elderly hypertensive patients at the Krian Public Health Center, Krian District, this was proved by the acquisition of sig values. = 0,000 (<0.05). Keywords: knowledge, the adherence of taking medication, hypertension